Strategi Komunikasi Organisasi Dalam Meningkatkan Kinerja Karyawan Cangkruk Vape Shop Sidoarjo - Noor Jannah; Tira Fitriawardhani; Julyanto Ekantoro (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2024)
This study examines the organizational communication strategies used by Cangkruk Vape Shop to improve employee performance, which are deemed ineffective in enhancing employee motivation, as evidenced by frequent tardiness and suboptimal work performance. This research employs a descriptive qualitative method. Data was collected through interviews with the shop owner, manager, store supervisor, and three operational staff of Cangkruk Vape Shop Sidoarjo. The main focus of the research is to identify and analyze the forms of communication strategies, both vertical and horizontal, used to improve employee performance. Data collection techniques include observation, interviews, and documentation. The research findings indicate that vertical and horizontal communication is used to create a positive work environment. This communication enhances employee work ethic and evaluates their performance through nine indicators. Improvements in employee performance are seen in increased creativity, initiative, and discipline.